2009
DOI: 10.1074/jbc.m109.010355
|View full text |Cite
|
Sign up to set email alerts
|

Yin-Yang Regulation of Adiponectin Signaling by APPL Isoforms in Muscle Cells

Abstract: APPL1 is a newly identified adiponectin receptor-binding protein that positively mediates adiponectin signaling in cells.Here we report that APPL2, an isoform of APPL1 that forms a dimer with APPL1, can interacts with both AdipoR1 and AdipoR2 and acts as a negative regulator of adiponectin signaling in muscle cells. Overexpression of APPL2 inhibits the interaction between APPL1 and AdipoR1, leading to down-regulation of adiponectin signaling in C2C12 myotubes. In contrast, suppressing APPL2 expression by RNAi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 20 publications
5
139
0
3
Order By: Relevance
“…Indeed, it was shown that the two adiponectin receptors, AdipoR1 and AdipoR2, are capable of homoand hetero-dimerization, and changes in their cellular ratio/amounts lead to alterations in AMPK phosphorylation (44). Activation of adiponectin signaling was also observed in C2C12 myotubes under depletion of adaptor protein, phosphotyrosine interaction, PH domain and leucine zipper containing 2 (APPL2), an AdipoR1-binding protein that acts as a negative regulator of adiponectin signaling (45). This study argued that under basal conditions, APPL2 interacts with AdipoR1 and inhibits downstream phosphorylation of AMPK and other signaling molecules activated by AdipoR1, while adiponectin treatment stimulates APPL2 disassociation from AdipoR1, thus leading to its activation.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it was shown that the two adiponectin receptors, AdipoR1 and AdipoR2, are capable of homoand hetero-dimerization, and changes in their cellular ratio/amounts lead to alterations in AMPK phosphorylation (44). Activation of adiponectin signaling was also observed in C2C12 myotubes under depletion of adaptor protein, phosphotyrosine interaction, PH domain and leucine zipper containing 2 (APPL2), an AdipoR1-binding protein that acts as a negative regulator of adiponectin signaling (45). This study argued that under basal conditions, APPL2 interacts with AdipoR1 and inhibits downstream phosphorylation of AMPK and other signaling molecules activated by AdipoR1, while adiponectin treatment stimulates APPL2 disassociation from AdipoR1, thus leading to its activation.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the regulation of glucose transport by adiponectin in skeletal muscle is dependent on the interaction of APPL1 with AdipoR (Mao et al 2006, 2009a, Zhou et al 2009, Xin et al 2011, leading to the subsequent activation of AMPK (Tomas et al 2002, Yamauchi et al 2002, Tsao et al 2003, Ceddia et al 2005, Mao et al 2006, Zhou et al 2009). Adiponectin-induced phosphorylation and activation of AMPK are primarily mediated through the cytosolic translocation of LKB1, which is mediated by PKC-z (Deepa et al 2011), and the interaction of LKB1 with APPL1, which localizes it to the cytosol (Zhou et al 2009, Fang et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed as our previously described protocol [6,7,28,29]. Briefly, 3T3-L1 adipocytes were lysed in lysis buffer containing 50 mmol/L HEPES, pH 7.6, 150 mmol/L NaCl, 1% Triton X-100, 10 mmol/L NaF, 20 mmol/L sodium pyrophosphate, 20 mmol/L β-glycerol phosphate, 1 mmol/L sodium orthovanadate, 10 μg/mL leupeptin, 10 μg/mL aprotinin, and 1 mmol/L phenylmethanesulfonyl fluoride.…”
Section: Western Blotmentioning
confidence: 99%
“…tors AdipoR1 or/and AdipoR2, adiponectin stimulates downstream events including activation of AMPK and p38 MAPK leading to an increase of glucose uptake and fat oxidation in muscle, and a reduction of fatty acid uptake and hepatic gluconeogenesis in liver [3][4][5][6][7][8]. Decreased adiponectin levels have been implicated with insulin-resistant states such as obesity and type 2 diabetes in both humans and animal models [1][2][3][4].…”
mentioning
confidence: 99%